A DFT study of silver decorated bismuthene for gas sensing properties and effect of humidity. (July 2022) - Isa, Muhammad; Ashfaq, Iqra; Majid, Abdul; Shakil, Muhammad; Iqbal, Tahir
Abstract: The decoration of the silver (Ag) atom on the buckled bismuthene (b-Bi) was explored in detail for sensing of gases (CO, CO2, SO, SO2, NH3, and H2 S) using density functional theory (DFT). The CO, SO, SO2, and H2 S gas molecules showed chemisorption while CO2 and NH3 physisorption behavior on b-Bi. The results of the adsorption energies show that Ag decoration on b-Bi is energetically stable. Decoration of Ag on b-Bi changed the behavior of b-Bi from semiconducting to metallic. The density of states (DOS) results indicate that CO, SO, SO2, and H2 S gases improve electronic properties by hybridizing gases with Ag-decorated b-Bi. Van der Waals interactions were involved to obtain the stable geometric structures of the b-Bi monolayer decorated with Ag with adsorbed gas molecules. Adsorption of CO on pure b-Bi changes from physisorption to chemisorption behavior in Ag-decorated b-Bi. Adsorption configuration, adsorption energy, charge transfer, DOS, transmission analysis, and the effect of humidity were studied in detail. Results of transmission for CO and SO gas molecules show that these gases induce larger changes to the system while CO2 and NH3 showed weak interaction or small change with pure Ag-decorated b-Bi. The humidity effect increased with the increase of adsorption energy, therefore, this kind of material could work even in the humidity condition. This suggests that the Ag-decoration improves the potential of b-Bi for the application of gas sensors. Graphical abstract: Image 1 Highlights: Ag-decorated b-Bi has been found a suitable material for the adsorption of gases (CO, CO2, SO, SO2, NH3, and H2 S). DOS shows that (CO, SO, SO2, and H2 S) gases improve the electronic properties due to the hybridization of gases with Ag-decorated b-Bi. The large amount of charge transfer between gases and Ag-b-Bi makes it good for gas sensing. The humidity effect shows that Ag-decorated b-Bi based sensors can work effectively in a humidity environment.